Feasibility Test of Transformer Insulating Oil Lifetime Based on Breakdown Voltage (bdv) and Furan Analysis - Dewi Cahya Febrina (Fakultas Teknik Universitas Bhayangkara, 2022)
Optimization of transformer performance in distributing electrical energy is determining by transformer insulating oilquality. Insulating oil temperature increases with the great of transformer workload released during the distributionof electric power to consumers. Then, it will be affected to the breakdown voltage (BDV) value and oil quality whichcan even lead to the insulating oil failure. This research is carried out by taking a sampling of new deck oil and usedoil at different temperatures. Then insulating oil is tested by using BDV test and Dissolved Gas Analysis (DGA) todetermining furan value and workability of insulating oil lifetime. Thus, this research expected to identify the feasibilityof transformer insulating oil lifetime based on breakdown voltage and furan value.